SISTEM PELAYANAN PENGELOLAAN SAMPAH DI KECAMATAN TAMPAN KOTA PEKANBARU - Dinata, Widia Wira; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Efforts to implement the waste management services business District of Tampan Pekanbaru issued Perda No. 5 of 2000 on Public Order, one of which includes environmental cleanliness . Environmental hygiene aims to keep K3 in an environment that is Beauty , Health and Sanitation . The services provided to the public in order to overcome the problem of garbage strewn everywhere. From observations of researchers in the field of more than 10 polling stations in the District Charming Pekanbaru City. The purpose of this study was to determine how the system of waste management services in the District Charming Pekanbaru City and to determine the factors that affect the system of waste management services in the District Charming Pekanbaru. This research was conducted in the District Charming Pekanbaru, using qualitative descriptive method, with the technique of collecting data through observation and interviews. This research was conducted by using a theory according to which Ratminto provide a quality service, with the Clarity, Timeliness, Responsibility and the Means and Prsasarana adequate.Results of this study concluded that the services rendered local government especially the District Handsome not implemented effectively. This is evident by the invisibility of trash are still scattered along the road, there are many wild TPS and garbage rotting in the gutters and drains. This happens because of a lack of coordination between the Head of Trantib related to the team and the lack of traction on the government in implementing the regulations. As well as the socialization of the janitor and the authority that has been given to RT, RW each region.Keyword : system, service, management